PEMBERDAYAAN POLA HIDUP KONSUMSI DENGAN PRINSIP EKONOMI SYARIAH BAGI NELAYAN SUKU BAJO DIPESISIR PANTAI BAJOE DI KABUPATEN BONE - Samsidar, Samsidar; Samad, Husaini (Universitas Mataram, 2024)
The aim of this activity is to overcome the dynamics of fishermen's problems in managing their management by providing assistance with scientific studies and education, basic training in managing their consumption patterns so that they can save and increase their income and welfare patterns. Likewise, the pattern of the lending and borrowing system for fishing communities requires assistance regarding the importance of contractual ties as a cooperation agreement between investors and borrowers. As for implementation methods, providing training on managing regular household consumption patterns through training assistance, Focus Group Discussions on how to manage income and usage.